EXPLORING THE ROLE OF LEADERSHIP AND ORGANIZATIONAL CULTURE IN ENHACING PUBLIC SECTOR INNOVATION IN MEDAN: AN SEM-PLS STUDY - Kepler Sinaga (The American Journal of Interdisciplinary Innovations and Research, 2024)
The purpose of this study is to find out and analyze the extent to which leadership variables and organizational culture affect the quality of public sector services through increasing public sector innovation as an intervening variable. The subject of this study is the population of Medan City, where the variables in this study are independent variables, namely leadership and organizational culture, dependent variables, namely public sector service quality variables, and intervening variables are variables that increase public sector innovation. The results of data analysis were carried out by SEM analysis using SMART PLS 4.0 software. The data collection technique is by observation and documentation studies. The research method uses a quantitative descriptive method of data analysis using the structural equation model (SEM) method, where the results of data processing using the SEM method are carried out with the PLS 4.0 application. From the results of the study, the existing conclusion is that partially, leadership variables and organizational culture affect the quality of public sector services and affect the improvement of public sector innovation. Simultaneously, leadership and organizational culture affect the quality of public sector services through the variable of increasing public sector innovation as an intervening variable. The more leadership serves, the more innovation will grow in public sector services which will eventually change the organizational culture that tends to be flexible and serve which makes the quality of public sector services improve its performance.